Percutaneous cervical laser diskectomy, thermoannuloplasty, and thermonucleoplasty; comparable results without surgery - Epstein, Nancy E. (Surg Neurol Int, 2017)
BACKGROUND: Utilizing the literature, the results of three different minimally invasive surgery (MIS) anterior cervical percutaneous operations for neck/mild radicular pain and magnetic resonance (MR)-documented “contained” (not extruded/sequestrated) discs were evaluated. Results were compared with patients treated nonsurgically for comparable/greater neurological compromise, and even more severe cervical disc disease. METHODS: There were three MIS percutaneous anterior cervical discectomy procedures. Anterior cervical laser discectomy ablated and vaporized disc tissue. The thermoannuloplasty used heat to contract collagen fibers to reduce disc volume. Thermonucleoplasty employed a low-temperature resister probe to promote disintegration and evacuation of small volumes of disc (e.g., some studies cited an average of just 0.09 mL of disc removed). These results were compared to those for the nonsurgical management of patients with comparable/greater neurological deficits, and more severe cervical disc herniations. RESULTS: The three MIS anterior cervical operations resulted in 80–90%+ improvement using Macnab's criteria. However, although the literature demonstrated similar 80–90+% improvement without cervical surgery, the latter patients were more neurologically compromised. CONCLUSIONS: For patients with pain alone/mild radiculopathy and “contained” discs on MR, three MIS percutaneous anterior cervical disc operations resulted in 80–90%+ improvement. Notably, similar 80–90%+ improvement was observed for comparable/more neurologically impaired patients with even larger cervical disc herniations treated nonsurgically. With such findings, where is the “value added” for these three MIS cervical operations?